Effect of crude oil exploration and exploitation activities on soil, water and air in a Nigerian community - Okonofua, Ehizonomhen S (Environmental technology, 2023)
The continuous degradation of environmental ecosystems (land, water and soil) resulting from crude oil exploration and exploitation activities continues to gain global attention. This study investigates the effects of crude oil exploration and exploitation activities on soil, water and air in the study area. Soil samples were collected in three replicates at depths of 0-15 and 15-30 cm at sampling distances of 20, 100 and 200 m a from core oil exploitation operation area and a control point. Water samples were also taken from within the study area and analyzed using standard procedures. Major pollutants concentrations of particulate matter (PM2.5 and PM10) of the air were also measured using Air Quality Index (AQI). The results reveal that the soil, water and air parameters measured mostly at 20 m from the core oil operation area compromise the allowable standards provided for healthy living. In the same manner, some results at 100 and 200 m were slightly higher than the recommended values in some cases of heavy metals and bacteria activities in the soil. The AQI at 20 m was far above the permissible limit provided by the Environmental Protection Agency while others are gradually drawing towards the limit given for each pollutant. To safeguard the health of the residents of the host community and oil field workers, there is a need for proper and frequent environmental monitoring and assessment by authorized regulatory bodies in Nigeria. This will prevent any future exposure which may endanger the lives of the dwellers